The therapeutic potential of natural products for treating pancreatic cancer - He, Xia; Wang, Ning; Zhang, Yu; Huang, Xiaobo; Wang, Yi (Frontiers in Pharmacology, 2022)
Pancreatic cancer is one of the most malignant tumors of the digestive tract, with the poor prognosis and low 5-year survival rate less than 10%. Although surgical resection and chemotherapy as gemcitabine (first-line treatment) has been applied to the pancreatic cancer patients, the overall survival rates of pancreatic cancer are quite low due to drug resistance. Therefore, it is of urgent need to develop alternative strategies for its treatment. In this review, we summarized the major herbal drugs and metabolites, including curcumin, triptolide, Panax Notoginseng Saponins and their metabolites etc. These compounds with antioxidant, anti-angiogenic and anti-metastatic activities can inhibit the progression and metastasis of pancreatic cancer. Expecting to provide comprehensive information of potential natural products, our review provides valuable information and strategies for pancreatic cancer treatment.